Mengembangkan Kreativitas Anak Tunagrahita melalui Kegiatan Prakarya di Sekolah SLB C Muzdhalifah - Noviar Panggabean; Rika Widya; Nurhaliza Heldiana; Sutini Sutini; Siti Aisyah Ginting Manik (Departement of Mathematics Education, 2024)
Fine motor skills in children with moderate mental retardation have an important role and influence in completing daily tasks and the level of independence of children with moderate mental retardation. This happens because children's daily activities involve coordination skills between the eyes and hands and the strength of small muscles. This study aims to examine the effectiveness of cutting techniques in improving fine motor skills in children with moderate intellectual disabilities. The research method used by researchers is a literature review, which is carried out by analyzing data from various previous research studies and trusted sources. The results of the research show that the cutting technique is an effective way to improve fine motor skills in children with moderate mental retardation. Therefore, it is necessary to pay attention to the application of cutting techniques at SLB C Muzdalifah for children with moderate intellectual disabilities in order to provide intervention to children and facilitate the development of fine motor skills in children with moderate intellectual disabilities. By providing appropriate intervention, teachers can use this technique as a tool that can help mentally retarded children who are facing difficulties developing fine motor skills.